Tata Kelola Pemerintah Dalam Pengembangan Kawasan Pariwisata di Desa Burai Kabupaten Ogan Ilir - Octaleny, Ellyza; Halbadika Fahlevi, Arry; Badriyansyah Fahlevi, Anggun; Fahlevi , A Rizal (STIA Bengkulu, 2024)
Tourism development is a significant phenomenon carried out by the government, this is due to changes in lifestyle in society, especially Indonesian people who prefer to travel. In the current era, the government relies heavily on the tourism sector to increase state foreign exchange and local revenue. However, the fact is that tourism development in Indonesia raises several new problems that need to be found for solutions so that the tourism sector can be superior. Based on this description, the Annisa Dwi Salfaritzi Palembang College of Administration and Government held community service activities through the theme of Government Governance in the Development of Tourism Areas in Burai Village, Ogan Ilir Regency. Tourism development aims to increase economic growth so that it can impact the welfare level of South Sumatra Province people in general, Burai Village, Ogan Ilir Regency in particular. The method used is socialization and assistance to the community. The solution to resolving government governance problems in developing the tourism area in Burai Village is forming a food business group, empowering environmentally based purun craftsmen groups, and mentoring and training craftsmen groups.